The « distance » approach in Michel Foucault’s literary writings, or how to inscribe the event in the structure - Jaquet , Gabriela M.; Madarasz, Norman Roland (Veritas (Porto Alegre), 2020)
Since the publication of the Dits et écrits, the place held by literature in Michel Foucault’s work has been clearly recognized by academic research, which has emphasized the Nietzschean approach of the reading made by the philosopher. Based on new publications and unpublished manuscripts, our paper considers this theme from another angle, that is, from structuralism in literary analysis and the philosophical stakes of the periodical Tel Quel in its relation with the French Nouveau Roman. By highlighting the importance of the concept of “distance” in his writings on literature, we aim to discuss how several of the notions created by Foucault are seen to be in dialogue with this larger theoretical constellation. As a case in point, we show the relation between structure and event, the conceptual pair at the center of philosophical debates in the 1960s, which guides us in the understanding of the tensions and adhesions of Foucault’s methodology with regard to structural analysis.